1977
DOI: 10.1007/bf00387157
|View full text |Cite
|
Sign up to set email alerts
|

The retention of photosynthetic activity by senescing chloroplasts of oat leaves

Abstract: The retention of photosystems I and II and or RuDP carboxylase activity in chloroplasts isolated from the first leaves of Victory oat (Avena sativa L.) seedlings was followed as the chloroplasts senesced in darkness. Both photosystems (PS) I and II retained their full activity after 3 days at 1°C, while even after 7 days at 1°C around 80% of the activity was still present. After 3 days at 25°C, PS I lost only 20% and PS II 50% of the initial activity. Acid pH increased the rate of decay of both systems, PS II … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

1978
1978
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…These experiments were repeated with young, expanding leaves and similar results were obtained. The intact chloroplasts contained no hemoglobin- (6,7), indicating that they contained proteolytic enzymes. It has also been shown that the processing of the precursor of the small subunit of RuBPCase involves a proteolytic cleavage carried out by an intrachloroplastic proteinase (8).…”
Section: -70mentioning
confidence: 98%
“…These experiments were repeated with young, expanding leaves and similar results were obtained. The intact chloroplasts contained no hemoglobin- (6,7), indicating that they contained proteolytic enzymes. It has also been shown that the processing of the precursor of the small subunit of RuBPCase involves a proteolytic cleavage carried out by an intrachloroplastic proteinase (8).…”
Section: -70mentioning
confidence: 98%
“…Leaf senescence also results in alterations in the absorption and fluorescence properties of photosynthetic pigments [3,6,19]. Recently a number of studies have been made on the changes of these photosynthetic parameters during senescence of chloroplasts in vitro [11,18]. But few attempts have been made to compare the kinetics of the degradation of chloroplasts during ageing of the organelles in vivo and in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…reported to be pH sensitive (6). We then examined thylakoidal and stromal performance both individually and combined in a reconstituted system fortified with adenine and pyridine nucleotides, Fd, and Pi in order to determine pretreatment-sensitive reactions.…”
mentioning
confidence: 99%